ALIANSI KERJA DALAM PROSES KONSELING ONLINE - Purnomo, Andreas Wisnu Adi; J.T. Lobby Loekmono (UNIVERSITAS BENGKULU, 2024)
This study aims to determine the level of work alliances that can be built in the online counseling process, and to find out how much influence work alliances have on the success of online counseling services that are carried out individually. This research was conducted using an experimental method. The type of experiment used is a single subject. Individuals who became the research sample were SMK students who had undergone an online learning process and experienced math anxiety. The data collection technique used the Abrivariatte Math Anxiety Rating scale made by Hopko, et al and the Work Alliance Inventory Short Version made by Munder, et al. The analysis technique used is simple linear regression using the application of Statistics Product and Service Solution (SPSS) version 16.0. Based on the analysis, it was found that the R value was 0.756, which means that the work alliance that was built in the counseling process has a strong relationship with the effect of the treatment given. The R2 value is 0.572, which means that the work alliance in the counseling process contributes 57.2% to the success of the treatment effect.